Representing Harmonious Society and Good Government as Portrayed in Confucius (2010) Movie by Hu Mei - Faqih, Ahmad (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2021)
Confucianism strongly emphasizes the principles of humanism, morals and ethics to guide humanity in realizing the meaning and purpose of life. More broadly, the principles of Confucianism about humanism, morality will form good social relations and create a peaceful and prosperous life. This article tries to figure out the significance relationship between society and government in creating peaceful human life. As in Confucianism peace itself is created through harmonious social relations in plural social conditions and under good governance. It is important to understand the concept of harmonious society as taught by Confucius by looking at the practice of community relations and a government. The findings of this study are a condition of a harmonious society will be formed when the authorities emphasize the principles of the teachings of humaneness, morality and ethics in regulating government and society. Mutual understanding between government and society through non-exclusionary relationship is also an indicator in achieving harmony and peaceful life.Konfusianisme sangat menekankan prinsip-prinsip humanisme, moral dan etika untuk membimbing umat manusia dalam mewujudkan makna dan tujuan hidup. Secara lebih luas, prinsip-prinsip Konfusianisme tentang humanisme, moralitas akan membentuk hubungan sosial yang baik dan menciptakan kehidupan yang damai dan sejahtera. Artikel ini mencoba untuk mengetahui signifikansi hubungan antara masyarakat dan pemerintah dalam menciptakan kehidupan manusia yang damai. Seperti dalam Konfusianisme, perdamaian itu sendiri tercipta melalui hubungan sosial yang harmonis dalam kondisi sosial yang plural dan di bawah pemerintahan yang baik. Penting untuk memahami konsep masyarakat harmonis yang diajarkan oleh Konfusius dengan melihat praktik hubungan masyarakat dan pemerintahan. Temuan penelitian ini adalah kondisi masyarakat yang harmonis akan terbentuk ketika penguasa menekankan prinsip-prinsip ajaran kemanusiaan, moralitas dan etika dalam mengatur pemerintahan dan masyarakat. Saling pengertian antara pemerintah dan masyarakat melalui hubungan non-eksklusif juga merupakan indikator dalam mencapai kehidupan yang rukun dan damai.